Resistance of cultivars of black currant to adverse abiotic factors of the summer period of arid zone of central Kazakhstan (Experimental biology, 2018)
The article presents the results of research of the resistance of 11 black currant cultivars to such abiotic factors of summer period as aridity and close location to the soil surface of limestone in the arid zone of Central Kazakhstan (Zhezkazgan Botanical Garden). Water content and water-holding capacity of leaves as a sign of drought-resistance of black currant cultivars were studied during 2015-2016. Least significance differences (LSD) between cultivars was established using Fisher’s tests. Differences between the means were ascertained with a multiple Duncan’s Test. There was not significant difference between the annual mean values of water content. According to the degree of drought resistance cultivars were divided into three groups. Agata, Altayskaya Pozdnyaya, Galinka and Glarioza are highly resistant. Kanakhama, Lentyay, Natasha and Rita are resistant. Sokrovishche, Chernyy Zhemchug and Yadrenaya are moderately resistant. The results of the have shown that almost all black currant cultivars are affected by chlorosis. The degree of damage ranged from 0 to 3 scores. Two-factor analysis of variance during three years showed that cultivars differed in degree of chlorosis (LSD = 0.96,p ≤ 0.5). There was no significant difference between the annual mean values of damages. Black currant cultivars were divided into three groups according to degree of damage with chlorosis. Chernyy Zhemchug, Galinka, Lentyay and Altayskaya Pozdnyaya are highly resistant to chlorosis. Agata, Glarioza, Rita and Yadrenaya are resistant. Kanakhama, Natasha and Sokrovishche are moderately resistant. The biological effectiveness of 0.5 % solution of Fe2SO4 after two treatments was high (from 66.7 % to 100 %).
Keywords: blackcurrant, abiotic factor, drought tolerance, lime chlorosis, Central Kazakhstan.